A trajetória histórica dos modelos de formação profissional do Serviço Nacional de Aprendizagem Industrial do Espírito Santo (1952-2002) - Teixeira, Zilka Sulamita (2018)
In this work, we analyze the historical trajectory of the professional training models of the National Service of Industrial Learning of the Holy Spirit from 1952 to 2002. Operating with critical thinking, based on Marxism, we undertake a historical reconstruction based on bibliographical research and documentary analysis. Our main sources were the Senai-ES reports (1955-2002), teacher training materials (FAI, FOFO, PETRA and FPBC) and school records of the period. We also discuss with Alves and Vieira (1996), Bologna (1980), Bennett (2015), Bryan (1983 and 1992), Fonseca (1986) and Muller (2009); Cunha (2000a, b and c), Fonseca (1986), Lima (2007), Medeiros (1987), Moraes (2003), Muller (2009) and Zuchi (2012). The historiographic effort on the screen allowed us to analyze the main permanences and discontinuities of the Senai-ES pedagogical models, generating a periodization that sought to present historically the implementation of training models based on the Occupational Methodological Series (SMO) from 1952 to 1992. This model for minors (1952-1959), through the consolidation of the multi-technical models with general training for minors and monotécnico for youths and adults (1960-1981), from 1981 to 1992, The institution undergoes a decline in the broader formation towards a closer formation, inclining to the monotech model without general education. In the 1990s, the Senai, admitting the "crisis" of its educational model focused on learning by doing (SMO), will initially incorporate with the Petra Model and, finally and definitively with the Training Based on Competencies (FPBC) in 2002. But we conclude that this movement has turned more to the question of financing and to the quest for accelerated service to business demands than for pedagogical reasons. To this end, the institution moves the center of its didactics from the concept of qualification to the notion of competences, from the concept of "formation to the market" to the "training market", emptying the project of a teaching for employment and assuming the teaching for employability.